Pembelajaran Gerakan Berbasis Bor: Kajian Eksperimental Keterampilan Passing Sepak Bola Anak Sekolah Dasar - Ahmad Juliarta Dwi Efendi; Hilmy Aliriad; Mohamad Da'i; Afdol Febriansyah (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The purpose of this study was to determine the effect of drill training methods on improving basic soccer passing skills in elementary school students. Materials and Methods. The research method used a quantitative experimental approach with a One Group Pretest-Posttest design. The research sample consisted of 15 students selected through purposive participant selection. Drill training was conducted once a week, lasting 45 minutes per session, for six consecutive weeks. Data collection consisted of a passing skills test covering aspects of technique, accuracy, and consistency. Results. The results showed a significant improvement in basic soccer passing skills after drill training. The average pretest score of 69.60 increased to 88.00 in the posttest. A paired sample t-test yielded a calculated t value of 15.05 with p = 0.001, indicating a significant difference between the results before and after treatment. This improvement indicates that repeated and structured drill training is effective in improving basic passing skills. Conclusions. The drill training method has a positive and significant effect on improving basic soccer passing skills in elementary school students. This method can be used as an effective alternative learning strategy in physical education.